Some threshold results of ecological competition model with reserve for one species and harvesting at fixed rates. - Sarma, B Bhaskara Rama (Journal of Experimental Sciences, 2012)
In the present investigation the stability analysis of a two-species competing ecological model with reserve for one species and harvesting at fixed rates is highlighted in view of principle of competitive exclusion due to Gause (1934). The model is characterized by a pair of non-linear system of ordinary differential equations. The equilibrium states are identified and a threshold theorem is derived to establish the stability of the co-existent equilibrium state.